Literature Study on Fiqh Muamalah Digital Business Transactions (e-commerce) - Yudi Siswadi; Andri Soemitra (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
The Digital Era or also known as the "Web 4.0" era where everything is converted into digital form. The muamalah sector is the single largest area of ​​digitization (buying and selling transactions). Advances in information technology have a positive impact on business innovation.transactions E-commerce have a positive impact on the widespread use of information technology and the internet today. E-commerce is the single most innovative aspect of Indonesian business. Currently, Indonesia is being hit by the Corona virus (Covid-19), and the government urges the public to adopt a healthy lifestyle by doing activities at home as a way to protect themselves. This condition will provide access to online buying and selling transactions, both through various digital platforms and those specifically related. The formal legality of digital/e-commerce business transactions has been regulated in Law Number 11 of 2008, Law Number 7 of 2014 concerning trade and Law Number 8 of 1999 concerning consumer protection and the MUI DSN with its Fatwa Number: 05/DSN- MUI/IV/2000 regarding the sale and purchase of Salam. The purpose of this study is to analyze the practice of e-commerce from the perspective of Fiqh Muamalat. The analytical method used is literature with qualitative approach analysis. Current studies show that e-commerce is a form of commerce that is synonymous with trading with as-salam. The practice of e-commerce in this way can also be considered to meet the requirements of as-salaam.